Review Literatur: Analisis Penyebab Pending Claim Berkas BPJS Kesehatan Pelayanan Rawat Inap di Rumah Sakit - Dhamigus, Yofen; Nurwahyuni, Atik (Jurnal Kesehatan Rajawali, 2024)
Health service providers include all Health Facilities that collaborate with BPJS Health in the form of First Level Health Facilities and Advanced Level Referral Health Facilities. This is the hospital's focus so that there are no obstacles in BPJS Health claims that could affect the hospital's operational cash became disturbed. The search for sources was based on the literature review method based on PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analysis). The two main data bases used in the search were Google Scholar and Pubmed. With the last search on February 17 2024. Inclusion criteria These are; (1) the article uses Indonesian or English; (2) this article was published in the last 2 years, namely 2022 to 2023; (3) quantitative and qualitative research; (4) the article is available in full manuscript form. From the search The keywords used are; "Pending Claim" AND "BPJS" OR "Health Insurance" OR "Claim Return". There were 5 articles reviewed systematically. Where 3 articles are quantitative research with 2 descriptive articles and 1 cross-sectional method, while the other 2 articles are qualitative with observation and interview methods. There were results that stated that the files were incomplete, the casemix team's knowledge in coding resulted in incorrect diagnosis coding, and the incomplete support carried out resulted in pending BPJS Health claims. All factors from input and process greatly influence the output. To reduce even greater losses and burden on hospitals, solutions need to be implemented immediately for each of these components which are still experiencing problems.